L’ethnographie et l’analyse des systèmes-mondes - Poncelet, Léo (Anthropologica, 2022)
In this article, the author develops his problematic of an ethnography in the modern world-system. By traveling beyond the closed horizon of the ethnologist and the historian, he rethinks the relation between actor and structure to articulate the hidden histories. Based on his previous field research, he shows that ethnography and world-system analysis are com plementary areas of knowledge. On the one hand, ethnography can curb the tendencies of analysts of world-systems to reify actions. On the other hand, besides being compatible with an anti-utilitarian approach, world-system analysis can bring about new cohesiveness to the anthropological project by prompting the ethnographer to insert short time on long time to better explain the mechanism of the structuration of local historical systems.